A comprehensive study of A357 alloy printability via laser metal deposition. (9th June 2023) - Furlan, Valentina; Kurtay, Tugay; Grande, Antonio Mattia; Previtali, Barbara
Abstract: Laser metal deposition (LMD) is one of the most important techniques in additive manufacturing (AM) thanks to the high flexibility of the process, which makes the production of free-form shapes possible. However, working with some materials presents some challenges. This is the case with aluminum alloys due to their reflectivity and their very high thermal conductivity. On the other hand, aluminum and its alloys are quite important in several industrial fields, including aerospace, among others, due to their mechanical properties with low density. In this work, LMD is applied on an A357 aluminum alloy. The techniques are investigated moving from a single-track approach up to multi-pass and multi-layer strategies. Densities, microstructures and mechanical performance are investigated as a function of process parameters. Porosities are reduced, resulting in overall densities of over 97% and microhardness values are in the range of 80–100 HV. Differences in mechanical performance are analysed considering different building directions, showing a dependency on loading direction and the distance from the substrate. Tensile tests reveal a promising performance for further investigation with the LMD technique. The obtained evidence is interesting for future trends where large and light components are required while maintaining the mechanical performance of traditional manufacturing methods. Moreover, a comprehensive study is done for the first time on A357 alloy that is deeply used in the aerospace and automotive fields. The investigation and definition of the best process parameters open the possibility of exploiting LMD technology in the production of wide components or for adding features to already existing components overcoming some limits of other AM technologies.